Pengaruh Media Digital dan Perubahan Struktur Sosial pada Gen-Z - Tri Utami; Jesica Imanuela Halolo; Reni Susanti; Faisal Dudayef (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This qualitative research, employing a literature review method, aims to dissect the massive influence of digital media on the shifting social structures of Generation Z. The findings indicate that technology has transformed interaction patterns from physical encounters to continuous digital communication, creating new forms of sociability that are expansive yet often superficial. The process of identity formation now relies heavily on self-curation in cyberspace, where digital metrics serve as benchmarks for validation, frequently triggering psychological pressure. This phenomenon also impacts the weakening of traditional parental authority due to the intergenerational digital divide. Although Gen Z is adept at building social capital through interest-based virtual communities, the risk of polarization remains a concern. Regarding value orientation, there is a shift toward authenticity and work flexibility that prioritizes personal meaning. Given its ambivalent impact on mental health, the study concludes that a synergy of robust digital literacy, strengthened family roles, and platform policies prioritizing user well-being is essential to navigate this social transformation.